1994
DOI: 10.2337/diacare.17.5.376
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Investigation of Perinatal Risk Factors for Childhood IDDM in Northern Ireland and Scotland

Abstract: Many reported risk factors are weak and show inconsistencies between studies. They may be secondary to more direct, as-yet-undiscovered risk factors. Although irrelevant in the majority of cases, the increased risk associated with delivery by cesarean section deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
102
4
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(134 citation statements)
references
References 0 publications
25
102
4
3
Order By: Relevance
“…Gestational diabetes is another possibility, but the proportion of mothers with gestational diabetes in these European populations is likely to be small [47], reducing the likelihood of marked confounding, and adjustment for gestational diabetes in seven of the studies [15,25,27] revealed little evidence of confounding. A further weakness of this study was that the reason for Caesarean section could not be investigated, as this was not available in the majority of studies, and therefore we were unable to confirm a report suggesting that any increased risk of type 1 diabetes after Caesarean section was most marked after elective procedures [24].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Gestational diabetes is another possibility, but the proportion of mothers with gestational diabetes in these European populations is likely to be small [47], reducing the likelihood of marked confounding, and adjustment for gestational diabetes in seven of the studies [15,25,27] revealed little evidence of confounding. A further weakness of this study was that the reason for Caesarean section could not be investigated, as this was not available in the majority of studies, and therefore we were unable to confirm a report suggesting that any increased risk of type 1 diabetes after Caesarean section was most marked after elective procedures [24].…”
Section: Discussionmentioning
confidence: 87%
“…The searches identified nine eligible articles using MEDLINE [15,17,[24][25][26][27][28][29][30]; a further article was identified from Web of Science [31] and another from EMBASE [32]. The more general MEDLINE search identified a further eight articles [33][34][35][36][37][38][39][40], and review of reference lists revealed another two articles [41,42].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of this research seem inconsistent, as some studies have concluded that high birthweight is associated with increased diabetes risk [8] or reduced diabetes risk [9], while others have shown no association with type 1 diabetes risk [10]. Interpretation of these findings is made more difficult because studies have reported associations using many different categorisations of birthweight [8,[11][12][13][14], with some [15,16] only reporting findings for the extremes of birthweight and others [17][18][19][20][21] not reporting their birthweight results in any detail, concentrating instead on other findings. This could lead to reporting bias if the decision to report birthweight findings was influenced by whether or not results were interesting or 'statistically significant'.…”
Section: Introductionmentioning
confidence: 73%